Analisis Efektivitas Program Beasiswa UPZ Tahun 2021 pada Mahasiswa UIN Sumatera Utara - Aini, Rija; Armayani, Reni Ria; Septiani, Bella Virnadya; Isnaini Ginting, Sri Rahmawati; Aprillia, Wina (Universitas Siliwangi, 2022)
This study aims to determine the effectiveness of the 2021 UPZ scholarship program for its recipients, namely North Sumatra UIN students. This research is a quantitative descriptive method by distributing questionnaires to students receiving UPZ scholarships in 2021 and obtained 50 people as research samples. The results show that the effectiveness of the 2021 UPZ Scholarship program for North Sumatra UIN students has been running effectively because it has received a percentage of 79.59% which has exceeded the 61% figure which is the benchmark that a program can be said to be effective if it exceeds that percentage. This scholarship is given for the collection of zakat funds for all lecturers and workers in the State Islamic University of North Sumatra. The distribution of zakat funds can be carried out if there are mustahik groups in the environment or related agencies.